Microfluidic Spinning Boosting Thermoelectric Performance of PEDOT:PSS Nonwoven Fabrics - Zhang, Yuhui; Qiu, Hui; Yang, Jian; Cao, Pengle; Wang, Yu; Xie, An‑Quan; Zhang, Ke‑Qin; Wang, Xiao‑Qiao (Nano-Micro Letters, 2026)
Organic thermoelectric generators hold great promise for powering wearable microelectronics, yet their performance is fundamentally constrained by the trade-off between electrical conductivity (σ) and the Seebeck coefficient (S). Herein, we develop a microfluidic spinning platform to fabricate PEDOT:PSS-based nonwoven fabrics with precisely engineered micro-/nanoscale physical and electronic structures, substantially enhancing thermoelectric performance. The intense shear field and in situ coagulation within microfluidic microchannels, synergized with H2SO4 treatment, promotes axial orientation and coil-to-linear conformational transition of PEDOT chains, achieving multiscale structural ordering for highly efficient charge transport in the resulting fibers. A subsequent controlled NaOH‑mediated dedoping process finely tunes the Fermi level and modulates energy‑dependent scattering, yielding a final σ of 2038 S cm−1 and an S of 29.7 μV K−1. Such integrated modulation enables effective optimization of the classic σ-S trade-off, ultimately yielding a power factor of 179.8 μW m−1 K−2. Furthermore, by integrating the fabric with an electrospun PVDF-HFP radiative-cooling layer, we demonstrate a radiation-modulated fabric device capable of maintaining an in-plane temperature gradient (ΔT ≈ 20 K) under natural sunlight and efficiently harvesting ambient solar-thermal energy. This study provides a versatile route for the fabrication of all-organic, flexible fabrics with high-performance thermoelectric functionality for wearable energy applications. Highlights: 1 A microfluidic spinning strategy is developed to fabricate PEDOT:PSS fibers with precisely engineered micro /nanoscale structures, effectively optimizing the trade-off between electrical conductivity and Seebeck coefficient. 2 The PEDOT:PSS fiber achieves a high conductivity of 2038 S cm−1 and a Seebeck coefficient of 29.7 μV K−1, yielding a remarkable power factor of 179.8 μW m−1 K−2 among organic thermoelectric fibers. 3 PEDOT fiber-based radiation-modulated nonwoven fabric device generates an in-plane temperature gradient of 20 K under sunlight (0.84 sun), enabling continuous solar thermoelectric energy harvesting for powering wearable microelectronics.